On the pH‐sensing properties of differently prepared tungsten oxide films. Issue 6 (3rd February 2014) - Drensler, Stefanie; Walkner, Sarah; Mardare, Cezarina Cela; Hassel, Achim Walter
<x xml:space="preserve">Abstract</x> In this paper, different preparation routes and designs for pH sensing metal/metal oxide electrodes are evaluated. Crystallographic changes in the oxide film are responsible for the pH‐sensing capability of tungsten oxide. As the present oxide structure is directly limiting the measuring range, as‐received tungsten oxide powders were heat treated to produce polymorphs of WO3, in an attempt to extend the measuring range. Furthermore, electrochemical oxide covered electrodes ranging from micro‐ down to nano‐dimensions have been implemented. Optional coating with Nafion, serving as a membrane material, allows shifting the measuring range even to strongly alkaline conditions.